Analysis Of Factors That Contribute To Unemployment Among Graduates at Kluang, Malaysia - HASSAN, MOHD SAYUTI; Supramaniam, Hakileswari (Advances in Social Sciences Research Journal, 2021)
In the current situation, unemployment in Malaysia, in particular youth unemployment, has increased due to certain unbalance in the labor market, aggravated by the current economic and financial crisis. For example, many other young graduates are currently unemployed, referring to research in a career which also normally doesn't really demand a graduate degree. The above dilemma is debatable, and the explanation behind it is that the level of education could not help to address the rate of unemployment, but could further increase the prevalent social problem. Human resources, especially young people, are perhaps the country's most valuable asset. The solution to the problem of youth unemployment is therefore a matter of great concern. It requires the development of modern employment policies that are in line with economic realities. Sampling methods are being used to select a sample from the general population. For the data analysis, the researcher used the Statistical Package for the Social Science (SPSS) tool. the data that are showed the dependent variable which is an effect of unemployment or reliability test has an excellent reliability value is 0.702. While the independent variables of reliability test of factors of unemployment has a good reliability which is 0.730. Hence, the questionnaire that have been constructed are valid.